Evaluating Outbreak Potential of Infections in Tropical Climates: Preventing the Pandemics of the Future - Mphande, Fingani Annie; Nyasulu, Peter Suwirakwenda (My University, 2025)
This book is a unique compilation that considers tropical diseases, including neglected, emerging, and re-emerging diseases, in the broader context of public health in society in low and middle-income countries. The book conducts a post-COVID-19 review on various public health issues in these settings, including mental health in people living with HIV, to diagnostics and disease prevention in resource limited settings. Following the onslaught of SARS-CoV2 on the human race and the significant healthcare challenges faced in low and middle-income countries, the pandemic brought to light the value of understanding infectious diseases that have great potential to degenerate into pandemics, and cause significant morbidity and mortality. The authors advocate that a focused, effective response and approach is essential moving forward. This includes—but is not limited to—clinical as well as public health intervention, vaccine development, and confronting the challenges of vaccine delivery, in the contexts of differential social and cultural paradigms and beliefs. This book provides pathways for future responses to such similar infectious diseases pandemics. Topics include connections between migration and Ebola, a highly infectious, outbreak-prone disease with devastating consequences; the multifaceted impacts of rabies, a neglected tropical disease affecting populations especially in low resource settings, as well as cholera, an outbreak-prone disease affecting populations in humanitarian settings and low income countries. Connecting public health, medical practice and policy, mental health, and society, this book is relevant to practitioners and scholars working in public health arenas and in areas of migration, development studies, and mental health.